Quality of life among young people in the Alps - Čataković, Dijana; Grünenwald, Annalena; Adolf, Henriette; Žakelj, Katarina; Kogovšek, Maja Kogovšek; Škrinjar, Rachela; Žemlja, Katarina; Audin, Aline; Jarosch, Julika; Holstein, Kathrin; Bailly, Océane; Berlot Veselko, Špela (Journal for Geography, 2025)
Measuring quality of life encompasses various dimensions, including individual perceptions and societal values. The Erasmus+ project Alpine Compass focuses on the quality of life for young people in the Alps, comparing their needs and challenges in France, Germany, Liechtenstein, and Slovenia through studies and interviews.This article combines literature analysis with interview opinions to identify new quality-of-life indicators. Quality of life is multifaceted, involving material conditions and subjective perceptions. Key results include the importance of a healthy environment, sustainable mobility, cultural offerings, mental health, and the impact of climate change on the future.